CASE STUDY AS AN EFFECTIVE METHOD OF TEACHING ENGLISH FOR SPECIFIC PURPOSES - Лещенко, Ганна (SWorldJournal, 2024)
The article deals with the notion of case-study method, analyzes the history of its development, defines a typical case structure, and describes the conditions for the formation of cases for teaching a foreign language as professionally oriented. Special